Answer:
n(x) = g(f(h(x)))
Explanation:
Given
![f(x) = x^3](https://img.qammunity.org/2022/formulas/mathematics/college/cyfp75p31hud84z0cxbzz3lbb3w5irjtf9.png)
![g(x) = x-7](https://img.qammunity.org/2022/formulas/mathematics/college/ap9wy6yj5oyutk27qpk37qmx6ckzjy2iek.png)
![h(x) = x + 2](https://img.qammunity.org/2022/formulas/mathematics/college/elkqj892oc87nd2z3z1pb73g4irkt04cv8.png)
Required
Which function represents
![n(x) = (x + 2)^3 - 7](https://img.qammunity.org/2022/formulas/mathematics/college/mlijcpcl0zdzj2kok5hmlmr1jc4iby83k7.png)
Start by solving for f(h(x)):
Given that:
and
![h(x) = x + 2](https://img.qammunity.org/2022/formulas/mathematics/college/elkqj892oc87nd2z3z1pb73g4irkt04cv8.png)
Substitute x + 2 for the x in f(x)
![f(h(x)) = (x + 2)^3](https://img.qammunity.org/2022/formulas/mathematics/college/h2xd22vm1tntlmlvej5tqztr15lu49wb07.png)
Next, solve for g(f(h(x)))
Given that:
and
![f(h(x)) = (x + 2)^3](https://img.qammunity.org/2022/formulas/mathematics/college/h2xd22vm1tntlmlvej5tqztr15lu49wb07.png)
Substitute (x + 2)^3 for the x in g(x)
![g(f(h(x))) = (x + 2)^3 - 7](https://img.qammunity.org/2022/formulas/mathematics/college/8k1xp5hb4qfog94mao7vl8pqnmgwsl00eq.png)
Recall that:
![n(x) = (x + 2)^3 - 7](https://img.qammunity.org/2022/formulas/mathematics/college/mlijcpcl0zdzj2kok5hmlmr1jc4iby83k7.png)
Hence:
![n(x) = g(f(h(x))) = (x + 2)^3 - 7](https://img.qammunity.org/2022/formulas/mathematics/college/lqqqikbprcf5qqpzizsyrjsjd1c2esxz0i.png)